2011
DOI: 10.1186/1745-6215-12-262
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of essential oil mouthwash with and without alcohol: a 3-Day plaque accumulation model

Abstract: BackgroundThe aim of this study was to evaluate the antiplaque effect of a new alcohol free essential oil mouthwash with respect to a control of an essential oil with alcohol mouthwash, using an in vivo plaque regrowth model of 3-days.MethodsThe study was designed as a double-masked, randomized, crossover clinical trial, involving 30 volunteers to compare two different essential oil containing mouthwashes, during a 3-day plaque accumulation model. After receiving a thorough professional prophylaxis at the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 41 publications
(43 reference statements)
2
43
0
5
Order By: Relevance
“…In addition, the AF‐EOMW showed no clear antiseptic effect compared with tap water rinse. Whereas many studies have assessed the antimicrobial effects of alcohol‐containing EOMW, with mostly positive results, a recent study showed that an EOMW could be less effective when it is alcohol‐free, which supports our findings. Another significant confounding factor that could explain the lack of detected differences in salivary pathogen levels within and between the study groups is the hyposalivation found in many participants.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the AF‐EOMW showed no clear antiseptic effect compared with tap water rinse. Whereas many studies have assessed the antimicrobial effects of alcohol‐containing EOMW, with mostly positive results, a recent study showed that an EOMW could be less effective when it is alcohol‐free, which supports our findings. Another significant confounding factor that could explain the lack of detected differences in salivary pathogen levels within and between the study groups is the hyposalivation found in many participants.…”
Section: Discussionsupporting
confidence: 89%
“…They rinsed twice a day for 3 days. EO with alcohol showed better plaque inhibitory effect (plaque index of 2.18 in whole mouth) than alcohol-free solution (plaque index of 2.46) [24].…”
Section: Differentmentioning
confidence: 86%
“…Chlorhexidine was effectively preventing and controlling gingivitis that could be used as a plaque control agent that showed the best results as an antiseptic effect. 8 Despite it was effectively as strong antiseptic action, chlorhexidine has side effects such as tooth pigmentation, changes in tasting sensation and the formation of supragingival calculus in long-term use. Other mouthwashes such as povidone iodine in long-term used would give side effects such as iodine sensitivity problems, local erythema, pain, mucosal erosion and major risks associated with thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…Other mouthwashes such as povidone iodine in long-term used would give side effects such as iodine sensitivity problems, local erythema, pain, mucosal erosion and major risks associated with thyroid function. 8,9,10 Various side effects arising from using of chemicals in the mouthwash was so many and significant, so it should take another alternative as a raw material to make a mouthwash with minimal side effects, economical and efficacious. The available alternative was the ingredients from the herb.…”
Section: Introductionmentioning
confidence: 99%